PENGARUH INDEPENDENSI, SKEPTISME DAN ETIKA PROFESI AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada KAP DI Kota Malang) - Fatmawati, Aida; Adji, Koenta; Wulandari, Retno (Jurnal Riset Mahasiswa Akuntansi, 2017)
Audit quality is the result of the auditor's performance in carrying out the task in question. Auditors are required to be able to produce high quality audits so that they have a great responsibility towards those who have an interest in the financial statements. This study aims to analyze the effect of independence, skepticism and professional ethics of auditors on audit quality. The population in this study are all auditors who work at the Public Accounting Firm in Malang. Sampling was done using convenience sampling method, and the number of samples was 60 respondents. This research is a form of explanatory research (explanatory research), and the research model is descriptive quantitative, namely data relating to numbers that still need processing and analysis for research purposes. The method of data collection is done by distributing questionnaires directly to auditors who work at the Public Accountant Office in Malang. Data analysis technique used in this study is multiple regression analysis techniques